The Effect of Fixed Asset Intensity, Inventory Intensity, Profitability, Leverage, and Board of Commissioners on tax Management - Arsella Zalianty; Inayaturrohmah; Aoliyah Firasati (PT FORMOSA CENDEKIA GLOBAL, 2024)
TThis research is focused on identifying the effects caused by fixed asset intensity, inventory intensity, profitability, leverage, and the presence of a board of commissioners on tax management practices. This quantitative study uses secondary data from manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) in 2020-2022. Samples were taken using purposive sampling method based on certain criteria, and 27 out of 63 companies that met the criteria were selected with a three-year period, resulting in a total of 81 sample data for this study. The data analysis technique used was multiple linear regression analysis conducted using the SPSS computer program version 25. The results showed that leverage and the board of commissioners have a positive impact on tax management practices, while profitability has a negative impact. However, in this study, fixed asset intensity and inventory intensity are not proven to have a significant impact on tax management practices